Mortality of workers at a nickel carbonyl refinery, 1958–2000. Issue 2 (18th January 2005) - Sorahan, T; Williams, S P
Abstract : Background: Excess risks of respiratory cancer have been shown in some groups of nickel exposed workers. It is clear, however, that not all forms of nickel exposure are implicated in these excess risks. Aim: To determine whether occupational exposures received in a modern nickel carbonyl refinery lead to increased risks of cancer, in particular nasal cancer and lung cancer. Methods: The mortality experienced by a cohort of 812 workers employed at a nickel refinery was investigated. Study subjects were all male workforce employees first employed in the period 1953–92 who had at least five years' employment with the company. Observed numbers of cause specific deaths were compared with expectations based on national mortality rates; SMRs were also calculated by period from commencing employment, year of commencing employment, and type of work. Results: Overall, standardised mortality ratios (SMRs) were close to 100 for all causes (Obs 191, SMR 96, 95% CI 83 to 111), all neoplasms (Obs 63, SMR 104, 95% CI 80 to 133), non-malignant diseases of the respiratory system (Obs 18, SMR 97, 95% CI 57 to 153), and diseases of the circulatory system (Obs 85, SMR 94, 95% CI 75 to 116). There were no significantly increased SMRs for any site of cancer. There was a non-significant excess for lung cancer (Obs 28, Exp 20.17, SMR 139, 95% CI 92 to 201), and in subgroup analyses a significantly increased SMR of 231 (Obs 9) was found for those 142 workers with at least five years' employment in the feed handling and nickel extraction departments. In the total cohort there was a single death from nasal cancer (Exp 0.10). Conclusions: The non-significant excess of lung cancer deaths may well be a chance finding, but in light of previous studies some role for nickel exposures cannot be excluded.